2020
DOI: 10.1002/pbc.28779
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hospital care volume on overall survival of children with cancer in Southern Brazil

Abstract: Purpose The purpose of this study was to analyze the effect of hospital care volume on the overall survival of children with cancer in Southern Brazil. Patients and Methods We performed a retrospective cohort study of 1378 cancer patients aged 0‐19 years, diagnosed with cancer between August 1, 2009 and December 31, 2015 in Rio Grande do Sul, who received hospital treatment in institutions affiliated with the Universal Health Care System (Sistema Único de Saúde [SUS]). Results Most children and adolescents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Research developed in the South region observed white individuals as the most affected by childhood and adolescent cancer. 12,16 Finally, a study carried out with the RHC records from all the units of the federation, in the period from 2000 to 2015, also verified a predominance of white children and adolescents. 21 This fact can be explained by the differences in human groups distributed in the country.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Research developed in the South region observed white individuals as the most affected by childhood and adolescent cancer. 12,16 Finally, a study carried out with the RHC records from all the units of the federation, in the period from 2000 to 2015, also verified a predominance of white children and adolescents. 21 This fact can be explained by the differences in human groups distributed in the country.…”
Section: Discussionmentioning
confidence: 82%
“…1 Male predominance was observed in this study and in another study involving children and adolescents, which covered the entire Brazilian territory 9 and isolated studies directed at states in different regions of the country. 4,[12][13][14][15][16] Males are more likely to have congenital diseases (chromosomal anomalies, monogenic syndromes, and nonsyndromic birth defects), which is associated with the risk of childhood cancers. 18 A higher number of records were found in the 0 to 4 years age group, corroborating a national study 9 and from different Brazilian states, 4,13,[15][16]18 as well as an international study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the small centers have a role in pediatric cancer care, this aspect could be an obstacle, as it is well recognized that higher volume hospitals, higher case volume providers and specialized pediatric oncology hospitals positively impact survival outcomes. [ 10 , 11 ]…”
Section: Discussionmentioning
confidence: 99%